Knowledge, Attitudes and Pratices (KAP) survey model for solid waste management in public park / Nurul Akmaniza Mohd Nasir ... [et al.] - Mohd Hashim, Nor Hanisah (Ts. Dr.); Hashim, Nur Idzhainee; Mohd Padzil, Amira Syuhada; Mohd Nasir, Nurul Akmaniza (UiTM Cawangan Negeri Sembilan, 2022)
The KAP survey is a quantitative method that usually conducted to collect reliable data on the knowledge (what is being known), attitudes (how people perceive) and practices (how people act) about general or specific issue. Introduction to KAP Survey Model Originated in the 1950s and it is widely used in the fields of health research, environmental science and management related field. KAP survey model is expected to generate raw data on the specific issue and be able to identify the gap of knowledge, beliefs among people and behavioural patterns performed. The outcome from the KAP survey model believed to help in program implementation planning and strongly influence decision making process. Data are collected by the researcher through a structured survey questionnaire that may include both qualitative and quantitative data collection. For the case of solid waste problem in a public park, it is believed that the issue is closely related to the attitudes among visitors. Awareness and attitudes among visitors believed as among of the factors that contributing to the solid waste problem especially in public park. Therefore, KAP survey model is seen as one of the effective method to provide baseline data in managing solid waste especially in public park.